Le tecnologie dell'informazione nella scrittura di Italo Calvino e Paolo Volponi Tre storie di rimediazione - Lima, Eleonora (Moderna/Comparata, 2020)
Over the last decade, considerable attention has been paid to how the information society and digital tools are changing the cultural and linguistic scene where literary production takes place. But what are the roots of this change and of the consequent debate? This book was created with the aim of studying how two of the most influential Italian writers of the second half of the 20th century, Italo Calvino and Paolo Volponi reacted to the initial diffusion of information technologies in the mid-fifties by wondering about the function of literary language and artistic creativity in a context of intelligent machines and mass information. Eleonora Lima carefully analyses some of the lesser known texts by the two authors, and discusses the opposition between the natural and the technological world in a society where information has become a product and a good to be exploited. She reconstructs the prerogatives and identities of biological and mechanical subjects, as defined by the then emerging cybernetic science. Finally, she investigates the political role of television representation in the years of dispute and terrorism. The comparative analyses, organized by thematic nuclei which are preceded by an overall historical and methodological framework, reveal the ways in which a 'remediation' process took place in writing, and show how, with new and often divergent strategies, the two narrators have faced the need to adapt literary tools to the changed communication context in a very personal way.